Never forget - Ortega, Missi Villan (Manila, Philippines : Philippine Publishing House, 2019)
Never Forget is a collection of 365 testimonies of faith, hope, love, divine providence, and other life lessons gleaned from the experiences of Mountain View College students, faculty, and alumni.
CAS
Daily Devotions for Juniors. Mountain View College Community.
Text in English
Keywords: Christian life -- Biblical teaching